(1R,3S)-3-Hydroxymethyl-N-isopropyl-2,2-dimethylcyclopropanecarboxamide - Jiangchun Zhong; Bing Zheng; Shicong Hou (Acta Crystallographica Section E, 2010)
The asymmetric unit of the title compound, C10H19NO2, prepared from (−)-1R-cis-caronaldehyde, contains two independent molecules. In the crystal structure, intermolecular O—H...O and O—H...N hydrogen bonds form an extensive three-dimensional hydrogen-bonding network.